Pendidikan Matematika Realistik Indonesia dalam Pembelajaran Mendalam (Deep Learning): Tinjauan Literatur - Rahayu, Chika; Setiani, Widya Rahmadatul; Yulindra, Devi; Azzahra, Luthfia (Faculty of Teacher Training and Education, 2025)
Deep Learning is being intensively studied as it emphasizes a mindful, meaningful, and joyful learning environment and process. Indonesian Realistic Mathematics Education (PMRI) is an approach to mathematics education that connects the learning materials with real-life situations. Based on the alignment between the definitions of the Deep Learning approach and the PMRI approach, this study aims to illustrate that Deep Learning can be achieved by integrating PMRI into learning activities. This research is a literature review that examines Indonesian Realistic Mathematics Education in the context of Deep Learning. In this study, four stages were carried out: designing the review, conducting the review, abstracting and analyzing the data, and writing and compiling the review result. The data for this study were collected from articles that met the inclusion and exclusion criteria outlined in the research methodology and filtered through Publish or Perish. Based on a review of 15 articles, the findings indicate that Indonesian Realistic Mathematics Education can be an alternative approach to achieving Deep Learning.